NON-FUNGIBLE TOKENS AND ART TOKENIZATION: A TOOL FOR MONEY LAUNDERING? - Bartnik, Krystian (Zeszyty Prawnicze, 2025)
This article examines the NFT market and art tokenization in the context of money laundering. It explores the evolution of the art market toward digitalization, the definition of NFTs, and their legal and technical aspects. Additionally, it highlights the rapid growth of the market and associated risks, such as fraud, sanction evasion, and money laundering. It discusses mechanisms for concealing illicit funds, as well as the lack of clear regulations and oversight of NFT platforms within the AML/CFT framework. It emphasizes the need for regulatory clarification, the establishment of transaction registries, and addresses other unresolved issues related to NFTs, including intellectual property protection and tax obligations.